Response of 'Mosambi' sweet orange (Citrus sinensis) to degreening, mechanical waxing, packaging and ambient storage conditions - LADANIYA, M S (The Indian Journal of Agricultural Sciences, 2014)
Response of 'Mosambi' sweet orange (Citrus sinensis Osbeck) fruits to degreening by ethylene in continuous flow process, mechanical waxing, packing iii vented polyethylene and ambient storage conditions ( 25Â± 5Â°C; 60-70 % RH ) was studied.Three pre-harvest sprays of carbendazim (500 ppm) were applied to fruits at 15 days interval. Respiration rate increased with ethylene treatment during degreening for 48 hr and then decreased gradually. Ethylene treated fruits turned yellow in colour within 48 hr while non-treated fruits remained green during that period. Weight loss in 'Mosambi' fruit was 8.89-10.05 % in Sta-fresh 451 wax coating compared with 2.93 % in polyethylene liner packing while wax coated fruit packed in polyethylene liner lost 2.03 - 2.29 % of their weight after 30 days. Decay was maximum (22.01%) after 30 days in non-waxed fruit packed in vented polyethylene as compared wito control (1.15%). Decay was mainly due to sour rot incited by Geofrichum candidum. Stem-end rots and Penicillium rots were not observed. There was no decay in fungicidal wax (Sta-fresh 451+1 000 ppm thiabendazole) coated fruit packed in polyethylene liner. Wax coating reduced respiration rate of 'Mosambi' fruits. Change of colour from green to yellow was quite slow in wax coated fruit as compared to non- coated fruit. After 30 days, yellow colour intensity was more in degreened + non - waxed fruit as compared with non-degree ned + non- waxed fruit. Fruits packed without polyethylene liner lost more juice and ascorbic acid and had more firmness, TSS and acidity content. Apperance and flavour score was highest after 30 days in degreencd fruit treated with Sta- fresh 451 wax (full strength or 1 :1 dilution) and packed in vented polyethylene lined CFB boxes.